Effectiveness of Providing Free Notary Services For the Underprivileged - Ridho Assyahid, Muhammad; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze the effectiveness of the implementation of the provision of free legal services in the field of notary by Notaries and identify obstacles and solutions in its implementation. This study uses a qualitative approach with a sociological juridical research type. The types and sources of data used consist of primary data and secondary data obtained through interviews and literature studies. Data analysis was conducted descriptively qualitatively. Based on the results of the study, it is concluded that the obligation of Notaries to provide free legal services in the field of notary to people who cannot afford it is regulated in Article 37 paragraph (1) of the Notary Law. This provision provides hope for people who cannot afford to continue to obtain notary services without charge. In practice, the provision of free legal services is carried out based on the Notary's assessment of the conditions and legal needs of the clients who come to him. In addition, the implementation of the provision of free legal services in the field of notary is a form of social responsibility of the Notary profession in providing access to justice. However, the effectiveness of its implementation still faces various obstacles, including limited outreach to the community, the high workload of Notaries, and operational costs that must still be borne even though the service is provided free of charge.